Hackathons for driving service innovation strategies: The evolution of a digital platform-based ecosystem - Maria Kamariotou; Fotis Kitsios (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Despite the fact that hackathons and digital innovation contests have emerged as substantial intermediaries in open innovation and entrepreneurship, knowledge about how hackathons and digital innovation contests impact innovation in cities is restricted. There is also a scarcity of models that aid in the organization of digital innovation contests. Based on the existing frameworks for contest organizations, the aim of this article is to present a case study which develops a framework for hosting and evaluating open data hackathons. The hackathon framework is developed from the organizer's viewpoint, and it has been executed in three digital innovation competitions in Thessaloniki. The suggested scheme adds new knowledge to the field of open data and digital innovation competitions while also providing practitioners with opportunities to host digital contests. Moreover, this framework offers hackathon organizers with regulations and resources to help them plan innovation contests that contribute to the betterment of an open data ecosystem.
Keywords: 650; digital services; ecosystem; hackathon; open innovation; service innovation